The Traits of Classical and Late Antiquity in Ausonius’ Poem Cupid Crucified - Tamošaitytė, Viktė (Literatūra, 2013)
Ausonius, a Roman poet of the fourth century AD, who lived in Gaul, was a controversial figure in Late Roman literature. He was compared to Cicero and Virgil by his contemporaries, but harshly criticized by the scholars of the nineteenth century. His life was also extraordinary: a humble grammar teacher, he became the tutor of a Roman emperor, later attained the rank of consul, and finally revealed himself as a poet. One of Ausonius’ most famous works is Cupid Crucified, which is the main subject of this article. The poem, written in flawless hexameter, tells an allegorical story whose heroines are the ghosts of mythical women who crucify Cupid in the underworld and torture him with the very same weapons that brought about their death in their unrequited love. At first glance, it seems that the poem is hardly different from those of Ovid or Virgil, but once you analyze it thoroughly it becomes clear that it was created in the twilight of the Roman Empire, with a deity on a cross and symbols of death (argumenta leti), not unlike those in the iconography of Christian martyr saints. However, the scene which at the start of the poem might seem to be almost a medieval forest pervaded with the mystical Celtic spirit turns out to be the classical underworld of the Aeneid. In his poems, Ausonius skilfully used and alluded to classical works, and he can rightfully be considered not only a poet, but also a gifted scholar. A translation of the poem in Lithuanian accentual hexameters is appended to the article.